Population dynamics of a freshwater amphipod from South America (Crustacea, Amphipoda, Hyalellidae) - Castiglioni,Daniela da Silva (2016)
Abstract This study aimed to characterize the population dynamics of Hyalella bonariensis Bond-Buckup, Araujo & Santos, 2008 from headwater spring in a rural area of state of Rio Grande do Sul, Brazil. Four samples were collected in August (winter) and October (spring) of 2012 and January (summer) and April (autumn) of 2013. Ovigerous females and precopula pairs were separated from other individual in the field. A total of 5,266 specimens were sampled, being 1,878 males, 2,073 females (including 240 ovigerous females) and 1,315 juveniles. The frequency distribution of size classes (measured as cephalothorax length, CL) was polymodal and bimodal in males and females, respectively. Males reach larger size than females. Sexual maturity of males and females was estimated at 0.40 and 0.38 mm for CL, respectively. Total sex ratio favored females, and these were more frequent in intermediate size classes, while males were more frequent in larger size classes. Ovigerous females and couples were found in four seasons, but both were more abundant in winter. Juveniles were also found in all seasons, being more frequent in winter and spring. These results showed that this H. bonariensis population has similar dynamics to other species of Hyalella Smith, 1874 from Brazil, but present variations when compared to other freshwater amphipods.